High Mortality Rates Among Patients With Non‐Traumatic Intracerebral Hemorrhage and Atrial Fibrillation on Antithrombotic Therapy Are Independent of the Presence of Cerebral Amyloid Angiopathy: Insights From a Population‐Based Study. Issue 15 (4th August 2020) - Ponamgi, Shiva P.; Ward, Robert; DeSimone, Christopher V.; English, Stephen; Hodge, David O.; Slusser, Joshua P.; Graff‐Radford, Jonathan; Rabinstein, Alejandro A.; Asirvatham, Samuel J.; Holmes, David
Abstract : Background: Intracerebral hemorrhage (ICH) risk is higher in elderly patients with atrial fibrillation on antithrombotic therapy as well as those with cerebral amyloid angiopathy (CAA). We investigated if mortality among patients with atrial fibrillation on antithrombotic therapy presenting with non‐traumatic ICH was influenced by underlying CAA. Methods and Results: We used the Rochester Epidemiology Project to identify 6045 patients with atrial fibrillation aged >55 years on anticoagulation or antiplatelet therapy from 1995 to 2016. Seventy‐four patients in this cohort presented with non‐traumatic ICH. Medical records including imaging data were reviewed to identify those with CAA and record baseline variables and outcomes of interest; 38 of our 74 patients (51.4%) (mean age 81.5 years) met Modified Boston Criteria for possible or probable CAA. Twenty‐six of 74 patients (35%) died during the first 30 days while 56 of the 74 (76%) patients died by 10 years follow‐up after index ICH. Overall mortality was not significantly different between the CAA and non‐CAA groups at any point of time during follow‐up ( P =0.89) even amongst patients restarted on anticoagulation +/− antiplatelet (n=19) ( P =0.46) or those patients restarted only on antiplatelet therapy (n=22) ( P =0.66). Three of the 41 patients who restarted on antithrombotic therapy had a recurrent ICH; these 3 patients met criteria for possible or probable CAA. Conclusions: Although more than half of our patients with atrial fibrillation on antithrombotic therapy and non‐traumatic ICH met Modified Boston Criteria for CAA, CAA did not significantly influence the high mortality seen in this cohort.